García Ayluardo, Clara, coord. Las reformas borbónicas, 1750-1808. México: cide, fce, Conaculta, inehrm, Fundación Cultural de la Ciudad de México, 2010. 360 pp. - Velasco Pedraza, Julián Andrei (2014)
null